Dysregulation of PP2A-Akt interaction contributes to Sucrose non-fermenting related kinase (SNRK) deficiency induced insulin resistance in adipose tissue - Jie Li; Ran An; Shuiqing Lai; Linlin Li; Simin Liu; Haiyan Xu (Molecular Metabolism, 2019)
Objective: We previously identified Sucrose non-fermenting related kinase (SNRK) as a regulator of adipose inflammation and energy homeostasis. In this study, we aimed to investigate the role of SNRK in insulin signaling in white (WAT) and brown adipose tissue (BAT). Methods: Adipose tissue specific (SNRK deficiency in both WAT and BAT) and BAT specific knockout mouse models were employed. Phosphoproteomic studies were conducted to identify the novel SNRK pathway regulating insulin signaling in adipose tissue. Results: SNRK ablation is sufficient to inhibit insulin-stimulated AKT phosphorylation and glucose uptake in both WAT and BAT. Phosphoproteomic study using SNRK deficient versus wild type BAT samples revealed 99% reduction of phosphorylation on Serine 80 of PPP2R5D, the regulatory subunit of Protein phosphatase 2A (PP2A). Drastic (142.5-fold) induction of phosphorylation on Serine 80 of PPP2R5D was observed in SNRK-deficient primary brown adipocytes overexpressing SNRK compared to control protein. In vitro phosphorylation reaction followed by targeted phosphoproteomic detection further confirms that human recombinant SNRK is able to phosphorylate human recombinant PPP2R5D. Dephosphorylated PPP2R5D promotes constitutive assembly of PP2A-AKT complex, therefore inhibits insulin-induced AKT phosphorylation and subsequent glucose uptake in both BAT and WAT. Knockdown of PPP2R5D in adipocytes can improve insulin sensitivity in adipocytes without SNRK expression. Conclusions: Our findings demonstrate that SNRK regulates insulin signaling through controlling PPP2R5D phosphorylation, which subsequently impacts PP2A activity and then AKT phosphorylation in both WAT and BAT. SNRK may represent a promising potential target for treating insulin resistance-related metabolic disorders. Keywords: Adipose tissue, SNRK, Insulin signaling, AKT phosphorylation, Phosphoproteomics